Glycomis quangtriensis (Rutaceae), a new species from Quang Tri province, central Vietnam - Le, Tuan Anh; Tagane, Shuichiro (Phytotaxa, 2024)
A new species of Glycosmis (Rutaceae), G. quangtriensis is described based on the specimens collected from the Limestone Razorback Hill and Rockpile Hill, in Huong Hiep Commune, Dakrong District and Cam Tuyen Commune, Cam Lo District, Quang Tri Province, central Vietnam. Morphological description, photographs, a distribution map, vernacular name, and preliminary conservation status are provided for G. quangtriensis. This species is characterized by shrubby habit 1.5 m tall, simple and subsessile leaves, elliptic-oblong lamina with undulate margin and auriculate base, by which combination it is clearly distinguished from all the previously known species in the genus.